Effectiveness and safety of a protocolized mechanical ventilation and weaning strategy of COPD patients by respiratory therapists - Kirakli, Cenk; Ediboglu, Ozlem; Naz, Ilknur; Cimen, Pinar; Tatar, Dursun (Journal of Thoracic Disease, 2014)
Introduction: Prior researches have showed that weaning protocols may decrease the duration of mechanical ventilation. The effect of these protocols on chronic obstructive pulmonary disease (COPD) patients is unknown. The purpose of this study was to evaluate the impact of an extensive mechanical ventilation protocol including weaning applied by a respiratory therapist (RT) on the duration of mechanical ventilation and intensive care unit (ICU) stay in COPD patients. Materials and methods: A novel mechanical ventilation protocol including weaning was developed and initiated for all intubated COPD patients by a respiratory therapist. Outcomes of patients treated using this protocol during a 6-month period were compared to those of patients treated by physicians without a protocol during the preceding 6 months. Results: A total of 170 patients were enrolled. Extubation success was significantly higher (98% vs. 78%, P=0.014) and median durations of weaning, mechanical ventilation and ICU stay compared with time to event analysis were significantly shorter in the protocol based group (2 vs. 26 hours, log rank P